Self-Efficacy and Health Status in Coronary Artery Disease Patients - Wantiyah Wantiyah; Mochamad Riko Saputra; Fitrio Deviantony (Universitas Airlangga, 2020)
Introduction: Coronary Artery Disease (CAD) impairs all aspects of the patient's life due to the decrease in physical function and lower quality of life, indicating an overall decreased health status. Self-efficacy as a psychological factor plays an important role in individuals maintaining a healthy lifestyle and improving their health status. The aim of this study was to analyze the correlation between self-efficacy and the health status of coronary artery disease patients.Methods: This study used an observational analytic research design with a cross-sectional approach. This study involved 112 respondents who were coronary artery disease patients in RSD Dr. Soebandi Jember obtained through the incidental sampling method. The data was collected using Cardiac Self-Efficacy (CSE) and Seattle Angina Questionnaire (SAQ). The data analysis used the Spearman rank test with a 95% CI.Results: The results showed that there was a significant relationship between self-efficacy and health status (p = 0,001, r = 0.307, α = 0,05). Self-efficacy was in good category (71,41 points) while health status was also in the good category (79,56 points).Conclusion: The low positive correlation between the two variables shows that the higher the value of self-efficacy, the higher the value of health status. Good self-efficacy through healthy living behaviors can increase the health status of coronary heart disease patients. It is important for nurses to improve the psychological aspect of the patients including self-efficacy when optimizing their self-care and health status.